MarkovFit: Structure Fitting for Protein Complexes in Electron Microscopy Maps Using Markov Random Field - Alnabati, Eman; Esquivel-Rodriguez, Juan; Terashi, Genki; Kihara, Daisuke (Frontiers in Molecular Biosciences, 2022)
An increasing number of protein complex structures are determined by cryo-electron microscopy (cryo-EM). When individual protein structures have been determined and are available, an important task in structure modeling is to fit the individual structures into the density map. Here, we designed a method that fits the atomic structures of proteins in cryo-EM maps of medium to low resolutions using Markov random fields, which allows probabilistic evaluation of fitted models. The accuracy of our method, MarkovFit, performed better than existing methods on datasets of 31 simulated cryo-EM maps of resolution 10 Å, nine experimentally determined cryo-EM maps of resolution less than 4 Å, and 28 experimentally determined cryo-EM maps of resolution 6 to 20 Å.